Observation of Higgs Boson Decay to Bottom Quarks - Sirunyan, A M; Tumasyan, A; Adam, W; Ambrogi, F; Asilar, E; Bergauer, T; Brandstetter, J; Dragicevic, M; Erö, J; Escalante Del Valle, A; Flechl, M; Frühwirth, R; et al. (Physical review letters, 2018)
The observation of the standard model (SM) Higgs boson decay to a pair of bottom quarks is presented. The main contribution to this result is from processes in which Higgs bosons are produced in association with a W or Z boson (VH), and are searched for in final states including 0, 1, or 2 charged leptons and two identified bottom quark jets. The results from the measurement of these processes in a data sample recorded by the CMS experiment in 2017, comprising 41.3 fb^{-1} of proton-proton collisions at sqrt[s]=13 TeV, are described. When combined with previous VH measurements using data collected at sqrt[s]=7, 8, and 13 TeV, an excess of events is observed at m_{H}=125 GeV with a significance of 4.8 standard deviations, where the expectation for the SM Higgs boson is 4.9. The corresponding measured signal strength is 1.01±0.22. The combination of this result with searches by the CMS experiment for H→bb[over ¯] in other production processes yields an observed (expected) significance of 5.6 (5.5) standard deviations and a signal strength of 1.04±0.20.